Assessing the promotion of clinical reasoning in classroom teaching among student nurses: A case of St Joseph's College of Nursing - Banda Bonyonga, Mtinkheni Wezi (2021)
The assessment of how clinical reasoning is promoted among student nursing and midwifery technicians followed the anecdotal reports from the public on the poor quality of client care provided by the nurses in the health facilities. These observations by the stakeholders pointed to the teaching and learning processes involved in the preparation of the nursing midwifery technicians. If the level of performance of the nursing midwifery technician is in question then the teaching and learning processes involved needs to be assessed because the educational level at which a student nurse is prepared makes the difference on how the nurse performs her duties in practice. This led to a concurrent exploratory mixed method study with the purpose of determining how clinical reasoning was promoted in classroom teaching among the student nurses. The population consisted nurse educators (n=18) and student nurses (n= 90). Quantitative data was collected from the educators and student nurses using questionnaires to determine the teaching styles of the educators, learning preferences and clinical reasoning levels of the student nurses. Qualitative data determined the educators and student nurses perceptions on the teaching and learning experiences from eight educators and three students’ focus groups. Quantitative data were analyzed using the statistical package SPSS Version 20.0 and descriptive statistics were run for frequencies, means and standard deviations. Content analysis was used for qualitative data. The results indicated that there was lack of diversity in the use of teaching styles among the nurse educators. The Expert Teaching Style was the most preferred (mean= 4.06 and SD=.981); the less preferred (mean= 3.55 and SD=1.24) was the Facilitator Teaching Style. The dominant teaching method was the lecture method; student nurses preferred lecture method but felt that interactive teaching methods were important in their learning processes and development of clinical reasoning abilities. Students also lacked diversity in their learning preferences as they (54.7%) preferred to learn together in a classroom environment. The learner centered learning environment where individual thinking, expression of own opinions and learning from peers was the least preferred (6.67%) by the learners. These results are in agreement with the learner dependence from the qualitative results. Therefore based on these results there is need for improvement of the teaching/learning processes in order to improve quality of nursing care provided in the health facilities in Malawi.